Postpartum emotional disorders — a narrative review - Roza Motyka; Urszula Sioma-Markowska (Ginekologia Polska)
Emotional disorders during pregnancy and the postpartum period affect many women worldwide and present a significant challenge in perinatal care. The first year after childbirth is particularly demanding for a woman’s emotional well-being, asitismarked by profound physical, emotional, and social changes. The aim of this article is to review and compare the latest data on the prevalence, risk factors, and treatment options for baby blues and postpartum depression. For this purpose, the electronic databases — including PubMed, NLM, MDPI, Europe PMC, and Google Scholar — were searched for recent English-language articles with full-text availability. The search terms included: postpartum depression, baby blues, maternity blues, postpartum depression prevalence, postpartum depression risk factors, postpartum depression treatment, online psychotherapy, and postpartum depression covid. The review was compiled and evaluated using SANRA (Scale for the Assessment of Narrative Review Articles).